2022
DOI: 10.1038/s42003-022-04316-6
|View full text |Cite
|
Sign up to set email alerts
|

A new confuciusornithid bird with a secondary epiphyseal ossification reveals phylogenetic changes in confuciusornithid flight mode

Abstract: The confuciusornithids are the earliest known beaked birds, and constitute the only species-rich clade of Early Cretaceous pygostylian birds that existed prior to the cladogenesis of Ornithothoraces. Here, we report a new confuciusornithid species from the Lower Cretaceous of western Liaoning, northeastern China. Compared to other confuciusornithids, this new species and the recently reported Yangavis confucii both show evidence of stronger flight capability, although the wings of the two taxa differ from one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 65 publications
0
0
0
Order By: Relevance
“…Here we recover key parametric data germane to the flight capabilities of C. sanctus and, for the first time, test hypotheses about the aerial performance of this species through flight modeling. It is important to highlight that there is growing evidence of varying flight modes among confuciusornithids (Wang et al, 2022). Consequently, while our study provides a reliable framework for understanding flight performance in C. sanctus, our conclusions need to be treated with caution if extrapolated to other confuciusornithids, particularly for taxa with different wing outlines such as Eoconfuciusornis zhengi, which appears to lack the distinct elongation of the distal primaries of C. sanctus.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Here we recover key parametric data germane to the flight capabilities of C. sanctus and, for the first time, test hypotheses about the aerial performance of this species through flight modeling. It is important to highlight that there is growing evidence of varying flight modes among confuciusornithids (Wang et al, 2022). Consequently, while our study provides a reliable framework for understanding flight performance in C. sanctus, our conclusions need to be treated with caution if extrapolated to other confuciusornithids, particularly for taxa with different wing outlines such as Eoconfuciusornis zhengi, which appears to lack the distinct elongation of the distal primaries of C. sanctus.…”
mentioning
confidence: 81%
“…While these studies have regularly concluded that C. sanctus had some sort of aerial locomotion, these aerodynamic interpretations have ranged from having minimal flight capabilities (Nudds & Dyke, 2010) to being able to perform a degree of gliding (Senter, 2006; or soaring (Peters & Ji, 1999), or to conduct powered flight but limited to short periods of time (Falk et al, 2016). What all these studies have in common is the assumption that C. sanctus was unable to perform prolonged periods of flight (although Wang et al (2022) recently suggested that the basal confuciusornithid Eoconfuciusornis zhengi was adapted for fast, longdistant flight). The present study focuses on a well-preserved, fully feathered specimen (NHMW 1997z0112/0001) of Confuciusornis sanctus (Figs.…”
mentioning
confidence: 99%
“… (A) Anchiornis right scapulocoracoid in lateral view (showing the medial and lateral crash L-shape), furcula in cranial view based on LPM-B00169 and left coracoid in cranial view (showing the subaquatic shape) based on BMNHC PH804 (originally right side) modified after Hu et al (2009) , Pei et al (2017) , and IVPP V14378 based on personal observation; (B) Eosinopteryx based on YFGP-T5197 modified after Godefroit et al (2013) ; (C) Xiaotingia based on STM 27-2 modified after Xu et al (2011) (originally no scale bar); (D) Serikornis based on PMOL-AB00200 modified after Lefèvre et al (2017) . (E) Archaeopteryx right scapulocoracoid based on Mexberg specimen modified after Wellnhofer (2009) , and left coracoid and furcula based on 10th specimen modified after Mayr, Pohl & Peters (2005) ; (F) Jeholornis right scapulocoracoid based on STM after O’Connor et al (2018) , left coracoid based on STM 2-49 and IVPP V13886 modified after Wang et al (2022a) , Wang et al (2022b) , furcula based on YFGP-yb2 modified after Lefèvre et al (2014) ; (G) Sapeornis right scapulocoracoid based on IVPP V12698, furcula and left coracoid based on IVPP V13276 modified after Zhou & Zhang (2003a) , Zhou & Zhang (2003b) ; (H) Confuciusornis right scapulocoracoid based on IVPP V13168 and GMV-2132 modified from Li (2010) , Chiappe et al (1999) ; furcula based on GMV-2131 modified after ( Chiappe et al, 1999 ), left coracoid based on IVPP V16066 modified after Li (2010) . (I) crown birds based on Gallus ; (J) Patagopteryx based on MACN-N-11 modified after Chiappe (2002) ; Rallus subadult (47 days) (K) and juvenile (17 days) (L) modified from Olson (1973) ; (M) Struthio modified from McGowan (1982) .…”
Section: Compare Of Pennaraptoran Pectoral Girdlementioning
confidence: 99%
“…1 ) ( Wu et al, 2021a ). Alternatively, separation between the scapula and coracoid evolved independently in Jeholornis , Sapeornis and Ornithothoraces or in a clade formed by Sapeornis and Ornithothoraces (the sister taxon to Ornithothoraces is alternatively resolved as either Sapeornis or the Confuciusornithidae in various published phylogenetic analyses) ( Gianechini et al, 2018 ; Wang, Stidham & Zhou, 2018 ; Agnolín et al, 2019 ; Wang et al, 2022a )–both interpretations are equally parsimonious.…”
Section: Compare Of Pennaraptoran Pectoral Girdlementioning
confidence: 99%
See 1 more Smart Citation